On the growth of a periodic meromorphic function with simple poles - Tėvelis, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Тевялис. О росте периодических мероморфных функций с простыми полюсамиV. Tėvelis. Apie periodinių meromorfinių funkcijų su paprastais poliais augimą